Principal Instructional Leadership within the Framework of Clinical Supervision - Gunawan, Imam; Benty, Djum Djum Noor; Wardani, Adetya Dewi (Universitas Negeri Malang, 2023)
The purpose of this study is to reveal the process of instructional leadership within the framework of clinical supervision. This research was carried out with a qualitative approach, participant-observer method. The participants of this study were principals and teachers. This research was conducted at MI Al Fattah, Malang City, Indonesia. The data were collected using observation technique, where the researcher observed the principal’s instructional leadership behavior in fostering teachers based on the clinical supervision framework. The data were analyzed using Mason’s analysis model, namely categories, codes and explanatory logic (Mason, 2020). The results conclude that the processes that can be used by school principals as instructional leaders within the framework of clinical supervision are identification of instructional problems, define and describe the problem, critical analysis, examine solutions, formulate action plans, implementation, and evaluate.